PENGARUH LAYANAN BIMBINGAN PRIBADI DAN KONSEP DIRI TERHADAP RASA PERCAYA DIRI SISWA - Mudjijanti, Fransisca; Thalar, Hubertus Ledung (Educatio Vitae, 2015)
There are two factors that affect the self-esteem of students, i.e. internal and external factors. Internal factors exist within students while the external factors come from the outside environment. In this case the most important of the internal factors is the self concept while the external factor is the school environment (including curriculum, good relationships with teachers, and learning infrastructure. The aim of this study is to determine the effect of private tutoring services and the self-concept of the students against the students’ confidence. The population in this study were the students of class VIII and IX of Saint Joseph Catholic Junior High School school year 2013/201. The number of respondents is 109 students. The sampling technique used is acidental sampling. The data obtained by using the scale questionnaire method is the private counseling service scale, the self-concept scale, and the self confidence scale. In this study the outher proposes three hypotheses: 1) The personal counselingservices  influence to the self-esteem of students, 2) The self-concept influencesto the self-esteem of students, 3) The personal counseling services and self-concept influence to the sel-esteem of students. The analysis technique used is the multiply linear regression techniques. The research proves; there is not influence of the private tutorial services to the students' self-confidence with t (0.109) <of the t table (1.990) the first minor hypothesis test. The Self-concept influences the self-confidence of students with t value (10.621) > t table (1.990). The major hypothesis testing shows the value of F (87.528) > of the F table value (3.08). Figures R = 0.789, shows that the correlation between the variables have a very strong cohesion. The effective contribution 0.623, means that 62.3% of the student self-confidence is influenced by personal counseling services and self-concept, while the remaining 37.7% is influenced by other variables not examined in this study. Keywords: the personal counseling services, the self-concept, the  self-confidence.